Aesthetic and cosmetic intervention in the treatment of melasma in an adult woman: A clinical case report (Research, Society and Development, 2025)
Melasma is an acquired skin hyperpigmentation characterized by symmetrical brownish spots on the face, resulting from excessive melanin production stimulated by hormonal, genetic, and environmental factors. Aesthetic and cosmetic interventions play a fundamental role in skin and emotional rehabilitation, improving skin uniformity and patients' self-esteem. This study aimed to analyze the effectiveness of aesthetic and cosmetic interventions in the treatment of melasma in an adult woman, highlighting the effects of the procedures, the active ingredients used, and adherence to treatment on improving hyperpigmentation and the patient's quality of life. This is a retrospective clinical case study with a descriptive and observational approach, involving document analysis and clinical evaluation of a 41-year-old patient with facial melasma. The results showed that the appearance of the spots occurred during the first pregnancy and intensified during the second, evidencing a strong relationship with hormonal variations. The patient's history revealed secondary amenorrhea due to continuous use of contraceptives and the presence of a breast cyst, factors that potentiate melanocytic activity. The patient had undergone previous treatments with kojic acid, tretinoin, and hydroquinone, but experienced relapses. The current intervention included supervised depigmenting therapies, rigorous photoprotection, and continuous aesthetic follow-up. A significant reduction in spots was observed in the malar, frontal, and perioral regions, resulting in greater skin homogeneity. It is concluded that an interdisciplinary approach favors clinical improvement, emotional well-being, and the patient's quality of life, reinforcing the importance of personalized protocols in the management of melasma.